The Healthy Young Men’s Cohort: Health, Stress, and Risk Profile of Black and Latino Young Men Who Have Sex with Men (YMSM) - Kipke, Michele D. (J Urban Health, 2020)
Young men who have sex with men (YMSM), especially YMSM of color, are at increased risk for a wide range of threats to their health and well-being. In this study, we recruited and surveyed an urban sample of 448 young African American/Black (Black), Hispanic/Latino (Latino), and multi-racial/ethnic YMSM, ages 16–24 years (mean = 22.3 years), about stressful life events, their health and mental health, their access to and utilization of care, and their involvement in risk-related behaviors. We found that the majority reported experiences of racism (87%) and homophobia (76%). A high percentage reported food insecurity/hunger (36%), residential instability (15%), financial hardship (63%), and conflict with family/friends (62%). The prevalence of risk behaviors was also high, including recent use of tobacco (46%), alcohol (88%), and marijuana (72%), and 41% tested positive for 1+ drugs. Furthermore, 26% tested positive for 1+ sexually transmitted infections (STIs). Over half (56%) reported being worried about their health, 33% reported having a chronic health condition and 31% a mental health condition, and 45% had wanted/needed mental health services during the past year. Further, 17% reported suicidal ideation/had planned a suicide attempt and 26% had ever engaged in self-injurious behaviors. Significant differences by race/ethnicity and HIV status included residential status/food insecurity, type of racism/homophobia, drug use, and STIs. These findings demonstrate how vulnerable this population is with respect to a wide range of structural and social determinants of health that may be important drivers of behavioral, health, mental health outcomes, and potentially long-term health disparities.